(untitled) (Journal of Parents and Teachers, 2017)
In this article we comment some questions about Pedagogical Leadership in educational centres. After narrowing the topic in general terms, some considerations are made about the main features that define a pedagogical leadership and the most important aspects and dimensions that shape it, which should be considered with a view to developing it in day-to-day practice of educational centres.